2022
DOI: 10.1039/d2en00220e
|View full text |Cite
|
Sign up to set email alerts
|

Detection and detoxification of imidacloprid in food samples through ionic liquid-stabilized CuNi alloy nanoparticle-decorated multiwall carbon nanotubes

Abstract: The development of resourceful catalysts with effective quantification as well as detoxification of insecticide is a major challenge in terms of food safety and sustainable agriculture. The present work reports...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…These results have been verified by recording CV profiles of Hg/KR‐1@MWCNT /GCE at different scan rate (20–220 mV s −1 ) in 5 mM solution of [Fe (CN) 6 ] 3−/4− at the scan rate 100 mV s −1 , indicating the enhancement in peak current of anodic and cathodic peak with potential shift (Figure 5E). Further, the linearity of the plot between the redox peak current vs square root of the scan rate (Figure 5F) explains the diffusion‐controlled process [35] …”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These results have been verified by recording CV profiles of Hg/KR‐1@MWCNT /GCE at different scan rate (20–220 mV s −1 ) in 5 mM solution of [Fe (CN) 6 ] 3−/4− at the scan rate 100 mV s −1 , indicating the enhancement in peak current of anodic and cathodic peak with potential shift (Figure 5E). Further, the linearity of the plot between the redox peak current vs square root of the scan rate (Figure 5F) explains the diffusion‐controlled process [35] …”
Section: Resultsmentioning
confidence: 85%
“…Further, the high‐resolution C 1s spectrum demonstrates the binding energy peaks at 284.5, 285.6, 287.61 and 288.59 eV has been ascribed to the C−C bond, C=C bond, HN−C=O bond and C=O bond peaks respectively of KR‐1@MWCNT/GCE (Figure 4C). [35] Similarly, the N 1s spectrum shows binding energy at 399.17 eV and 400.14 eV which is due to presence of N of ‐HN‐CO‐NH‐ group of KR‐1 and ‐HN(+)‐ respectively (Figure 4D). The O 1s spectrum indicate the peak at 531.98 eV for the C=O (Figure 4E).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…6A). 48 The effect of pH on the electroreduction of the AZM pesticide at Hg/IL@MWCNTs was investigated in the pH range of 2-12, depicting a slight change in the current intensity (Fig. S23 †).…”
Section: Scan Rate Ph Studies Stability and Reproducibilitymentioning
confidence: 99%
“…18 Furthermore, Singh and co-workers have reported various MWCNTs-modified composites for the recognition of toxic pollutants. [19][20][21][22] Apart from this, ionic liquids exhibit good cation-π interaction with MWCNTs, thus effectively preventing damage to the extended conjugation and conductive properties of the MWCNTs. [22][23][24][25] The literature studies reveal that there is no such material reported which is capable of simultaneously removing mercury metal and the azinphosmethyl pesticide from contaminated water.…”
Section: Introductionmentioning
confidence: 99%